PERAN AMIR MACHMUD DALAM PELAKSANAAN PEPERA 1969 - Andri Yunas Suryana; Andi Suwirta; Moch Eryk Kamsori (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2017)
This research entitled as “Peranan Amir Machmud dalam Mempertahankan Pemerintahan Soeharto 1969-1982”. The main problem in this research is “How deep the role of Amir Machmud in maintaining Soeharto’s government 1969-1982?”. The hictorical method used in this research, that is consisting heuristic, critical sources, interpretation, and historiography. To deepen the analysis, the interdisipliner approach such as sociology and political science was used in this research, such as role, political stability, and general elections concepts also there was Patron-Client and Structuration theories. Amir Machmud was a prominent figure during Orde Baru period. Amir Machmud was born at Cibeber, Cimahi city and had successful military career during New Order era. Amir Machmud held position as minister of domestic affairs in 3 periods. As a minister, he had successfully carry on some urge problems to government, like PEPERA problem that considered as fraudulence because unappropriate based on New York agreement by international affairs. Keywords: Amir Machmud, Role, West Irian, PEPERA.